PENGARUH KOMPETENSI GURU GEOGRAFITERHADAP HASIL BELAJAR PESERTA DIDIK DI LINGKUNGAN MADRASAH ALIYAH SE-KKM 01 CILILIN KABUPATENBANDUNG BARAT - Setiawan, Didin (2012)
Current issuesconcerningthe education processis the lowcompetency ofteachers.Thusthis studyidentifiesandgivesaconcretepicture ofhowthe influence ofteachers'competenceinteachinggeographyin all ofMadrasahAliyahin WestBandungregencytowardsstudent learning outcomes withthe number of teachersas many as40 people(a sample) andstudent learning outcomes(UNin 2011)as many as1137takenfor thesample of196students. The research methodused is explanatorysurveymethods, usingdescriptiveanalysisandverificative analysis. Hypotheses testedby describingthe results ofpath analysis.independent variables,namely: Pedagogiccompetence(X1), personalcompetence(X2), socialcompetence(X3), professionalcompetence(X4), andthe dependent variableis thestudy result of studentsof Geography(Y). The results showedthat thecompetenceof teachersof MadrasahAliyahin all of KKM01CililinWestBandungregency is in goodclassifaction. While the results ofstudent learningin MadrasahAliyahin all ofKKM01CililinWestKab.Bandungclassifiedquite well. Positiveand significantinfluence onteachers 'pedagogic competenceofstudent learning outcomes.Pedagogicalcompetenceof teachershave a significant effect(14.51%) to thestudents learning outcomes, teachers'personalcompetencehave a significant(7.75%), the teachers'socialcompetencehave a significant effect(6.61%),teachers'professionalcompetencehave a significant effect(12.44%). Simultaneouslyteacher competences,includepedagogical, personal, social andprofessional,have a significant(41%) to thestudent learning outcomesatMadrasahAliyahin all of KKM01CililinWest Bandung Regency. Teachers'competencescontribute positively tostudent learning outcomes.Suchcircumstancesshouldbe maintainedevenimproved. Tocreatesuch circumstance,teachersneed toimproveknowledgeandskills inteaching and learning,eitheron its own initiativeorthe initiative ofthe other partiesconcerned.